Knowledge and attitudes of medical students about clinical aspects of congenital cytomegalovirus infection in newborns: A nationwide cross-sectional study in Greece - Benou, Sofia; Hatzidaki, Eleftheria; Kalaintzi, Anna; Grivea, Ioanna; Baltogianni, Maria; Giapros, Vasileios; Thomaidou, Agathi; Sarafidis, Kosmas; Tsichla, Sofia; Sinopidis, Xenophon; Papachatzi, Eleni; Karatza, Aggeliki; et al. (Frontiers in Medicine, 2023)
Introduction: Cytomegalovirus (CMV) is the most frequent cause of congenital infection worldwide causing severe morbidity in newborns, infants, and children. Despite the clinical importance of congenital CMV (cCMV) infection, studies conducted so far indicate that there is limited awareness in the medical community in the field. The aim of this study was to assess Greek medical students' knowledge on cCMV infection. Methods: We performed a questionnaire-based nationwide cross-sectional study. A convenience sample of medical students from seven medical schools was enrolled. Results: Of the 562 respondents, 54,8% considered themselves undereducated on cCMV infection. However, almost half of the participants could correctly recognize some basic principles of cCMV infection including ways of transmission, diagnosis and treatment, while there were aspects of cCMV infection with knowledge deficit. The year of study had a positive impact on the level of knowledge with students of higher years of study being of more sufficient education on the specific topic. Conclusion: Overall, our study indicates a discrepancy between self-reported awareness and the level of knowledge among medical students in Greece.Further educational opportunities about cCMV should be offered, particularly in areas of the curriculum involving the care of women and children. Establishing medical students' solid background on the disease burden and educating them about preventative strategies for at-risk populations, should be the main pillars of such efforts in order to promote confidence in managing these cases in their future professional careers.